Decisions Relating to Cardiopulmonary Resuscitation : commentary 2: Some concerns - Luttrell, Steven (Journal of medical ethics, 2001)
In March of this year the British Medical Association (BMA), the Resuscitation Council (UK) and the Royal College of Nursing (RCN) published guidelines outlining the legal and ethical standards for decision making in relation to cardiopulmonary resuscitation (CPR).1 The guidance follows a year of increasing public awareness and concern about the issue and builds upon joint guidance issued by these institutions in June 1999.In April 2000 Age Concern issued a press release stating that “some doctors are ignoring national guidelines on the resuscitation of older people” and indicating that they had information on cases that had come to light in their campaign against age discrimination. Age Concern went on to say that older people have found “not for resuscitation” recorded in their medical notes without their agreement or knowledge.During the same month Professor Shah Ebrahim wrote a leader in the British Medical Journal stating that doctors regularly issue “do not resuscitate” orders for patients without their knowledge.2 He claimed that black people, alcohol mis-users, non-English speakers and those with HIV are more likely to get a “do not resuscitate” order, suggesting that prejudice is influencing medical decisions.This combination of events was followed by intense press and media interest in the way in which decisions were being made about cardiopulmonary resuscitation. Such was the level of concern that a health service circular was issued to all National Health Service (NHS) trust chief executives in September 2000 asking that appropriate resuscitation policies be in place which respect patients' rights, are understood by …